Crucial Parameters and Optimization of High-Speed Bearingless Drives - Hubert Mitterhofer; Siegfried Silber (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Bearingless drives integrate the functionality of magnetic bearings and an electric machine into a single device. While this integration allows very compact drives offering all advantages of magnetic levitation, the design process becomes significantly more complex. This work deals with the numerous topological and geometric design decisions which need to be taken for such a bearingless drive. Additionally, the definition of suitable optimization targets for the electromagnetic simulation process is outlined. The proposed guidelines generate a complex relationship of different dependencies which is then fed into the MagOpt optimizer for the design of a high speed bearingless disk drive, which allows verifying the optimization results through measurement results from two prototype drives.